El “costo oculto” del deterioro del suelo durante el proceso de “sojización” en la región de Arrecifes, Argentina - Zazo, Francisco Eduardo; Flores, Claudia Cecilia; Sarandon, Santiago Javier (Revista Brasileira de Agroecologia, 2011)
“Arrecifes”, located in the Pampas region, has undergone an intense process of soybean production inthe last 20 years, due to its higher economic profitability, which could have led to negative balances of nutrients andloss of soil carbon. This degradation of natural capital would involve a "hidden cost" that has not been taken into account when choosing technologies. The aim of this study was to quantify the soil degradation and expressed in physical and monetary values. Fertilizer inputs only partially cover the export of nutrients by soybean, maize and wheat, so the balance of N, P, K, Ca, Mg and S in the region were negative in all years of theperiod. The soybean crop was responsible for 83%, 89%, 91%, 95%, 75% and 77% of the losses of N, P, K, Ca, Mg and S, respectively. The carbon balance was negative every year for the soybean crop, which meant a loss of 163.969 t of carbon over the entire period. The total cost of replacing lost nutrients and carbon was worth US$ 286.383.247 of which 87% corresponded to soybeans. It is concluded that the process of soybean production in Arrecifes locality, led to a deterioration of the region's natural capital through increased nutrient losses and soil carbon that was not taken into account in the cost-benefit analysis.